Colourimetric and fluorimetric substrates for the assay of limit dextrinase. (March 2015) - Mangan, David; McCleary, Barry V.; Cornaggia, Claudio; Ivory, Ruth; Rooney, Edward; McKie, Vincent
Abstract: The measurement of limit-dextrinase (LD) (EC 3.2.1.142) in grain samples such as barley, wheat or rice can be problematic for a number of reasons. The intrinsic LD activity in these samples is extremely low and they often contain a limit-dextrinase inhibitor and/or high levels of reducing sugars. LD also exhibits transglycosylation activity that can complicate the measurement of its hydrolytic activity. A minor modification to the industrial standard Limit-Dextrizyme tablet test is suggested here to overcome this transglycosylation issue. In addition, two new substrates are described that can be adopted for use in an auto-analyser format. 4, 6- O -benzylidene-2-chloro-4-nitrophenyl-β-6 3 -α-d -maltotriosyl-maltotrioside (BzCNPG3 G3, Hexachrom) is not susceptible to transglycosylation and serves amiably as a routine quantitative assay tool with the potential to run kinetic assays due to the low p K a (∼5.5) of the chromogenic moiety while 4, 6- O -benzylidene-4-methylumbelliferyl-β-6 3 -α-d -maltotriosyl-maltotrioside (BzMUG3 G3, Hexafluor) was found to be susceptible to transglycosylation with LD. It is anticipated that Hexafluor may find extensive use in applications where high sensitivity is required such as high throughput screening studies. Highlights: Transglycosylation issue with Limit-Dextrizyme is easily resolved. Novel, selective, enzyme-coupled assay for the measurement of limit-dextrinase is reported. Nitrophenyl-functionalised substrate provides chromophore for simple quantitative detection. Methylumbelliferyl-functionalised substrate provides fluorophore for increased sensitivity. Kinetic assay format possible for BzCNPG3 G3 (Hexachrom).